CESM2 Last Interglacial at 127ka control ... - Berdahl, Mira; Leguy, Gunter; Lipscomb, William; Otto-Bliesner, Bette; Brady, Esther; Tomas, Robert; Urban, Nathan; Miller, Ian; Morgan, Harriet; Steig, Eric (UCAR/NCAR - Research Data Archive, 2024)
We examine results from two transient modeling experiments that simulate the Last Interglacial period (LIG) using the state-of-the-art Community Earth System Model (CESM2), with a focus on climate and ocean changes relevant to the possible collapse of the Antarctic ice sheet. The experiments simulate the early millennia of the LIG warm period using orbital forcing, greenhouse gas concentrations and vegetation appropriate for 127ka; in the first case (127ka) no other changes are made; in the second case (127kaFW), we include a 0.2 Sv freshwater forcing in the North Atlantic. Both are compared with a pre-industrial control simulation (piControl). In the 127ka simulation, the global average temperature is only marginally warmer (0.004 degrees C) than in the piControl. When freshwater forcing is added (127kaFW), there is surface cooling in the NH and warming in the SH, consistent with the bipolar seesaw effect. Near the Antarctic ice sheet, the 127ka simulation generates notable ocean warming (up to 0.4 degrees ...